Simplified micrometric surface characterization of different implant surfaces available on the Brazilian market - Carmo Filho, Luiz Carlos do (2018)
Aim: This study characterized the implant surfaces available on the Brazilian market in terms of topography, chemical composition, and roughness. Methods: The following brands were selected according to their surfaces: Kopp (Ko), Signo Vinces (Sv), Neodent (Ne), Osseotite (Os) NanoTite (Nt), SIN (Si), Titanium Fix (Tf), conventional Straumann (Str), Active SLA (SLA). The morphological analysis and the alloy impurities and implant surface contaminants were analyzed by SEM-EDS. Surface roughness parameters and 3-D reconstructions were obtained by laser microscopy (20x). Two distinct areas were evaluated: i) the cervical portion (no surface treatment), and ii) the middle third (treated surface). Results: The characterization of the implant surfaces by SEM showed morphological differences between the thread geometries and surface morphology at 800x and 2000x magnification. The EDS elemental analysis showed a predominance of titanium (Ti) for all implants. The SLA surface showed only peaks of Ti while other implants brands showed traces of impurities and contaminants including Al, C, PR, F, Mg, Na, Ni, O, P, and SR. The implant surface roughness in the cervical portion did not exceed Ra 0.5–1.0 μm, constituting a minimally rough surface and obtaining acceptable standards for this region. Only Nt, Str, and SLA presented Ra above 2 μm in the middle third area showing a rough surface favorable for osseointegration. Conclusion: This study concluded that there is no established standard for morphology, chemical composition and implant surface roughness that allows a safe comparison between the available dental implant surfaces. National implant brands generally contain more impurities and surface contaminants than their international counterparts and were consequently more sensitive to the surface treatment techniques.